2023
DOI: 10.1088/1755-1315/1231/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal adsorbents for glycerin purification

Dilnoza S Salikhanova,
Dilafruz D Savrieva,
Muslima I Karabaeva
et al.

Abstract: The article is devoted to the research of the chemical composition of coals. The main goal of the research is to choose the method of its enrichment. The authors established that after the enrichment of coal, the ash content sharply decreased due to the washing off of its inorganic part. The process of coal enrichment, at a ratio of 1:2 (coal: water) has a positive effect on reducing the ash content by 1.3 times. Based on the data obtained, it was found out that the enrichment process in the coal production ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The density, on the other hand, changes slightly, and the water retention decreases from 60 to 6 cm3/30 min. Based on the research results, it can be concluded that by selecting the appropriate concentration of PAA, the technological parameters of the solutions obtained with its use can be purposefully regulated [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…The density, on the other hand, changes slightly, and the water retention decreases from 60 to 6 cm3/30 min. Based on the research results, it can be concluded that by selecting the appropriate concentration of PAA, the technological parameters of the solutions obtained with its use can be purposefully regulated [9][10][11].…”
Section: Resultsmentioning
confidence: 99%